KONTRIBUSI PELAKSANAAN TUGAS SUPERVISOR TERHADAP KUALITAS KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL GURU PAI MTsN SE-KABUPATEN SOLOK - Dudu Wardana (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
Based on observation in the field, the researchers find that the pedagogic and professional competence all PAI teachers MTsN in Solok Regency are relatively low. The researcher think that the lack of pedagogic and professional competence all PAI teachers MTsN in Solok Regency was due to the low contribution about the implementation of the supervisor task. The study population were all PAI teachers  MTsN in Solok Regency as 190 peoples. The samples are 48 peoples obtained by using proportional startified random sampling technique. The data were collected using a questionnaire technique using a Likert scale. The first and second hypotheses were tested using simple regression techniques and correlation, while the third hypotheses with multiple regression technique and correlation. The result of data analysis showed thats: (1) the duty supervisur has contribution significantly 93,3% to all PAI theachers  MTsN in Solok Regency, (2) the implementation of the task supervisor contribute significantly 93,5% to all PAI teachers MTsN in Solok Regency competence and professional, (3) the implementation of task supervisor has contribution to the supervisor simultaneously and significantly 93,5% the pedagogic competence and professional competence all PAI teachers MTsN in Solok Regency. It was concluded that the implementation of the task supervisor is an important one that can influence and professional compeence of all PAI teachers  MTsN in Solok Regency , beside other varibles not be examined in this study.